Binding lies - Merzel, Avraham; Ritov, Ilana; Kareev, Yaakov; Avrahami, Judith (Frontiers in Psychology, 2015)
Do we feel bound by our own misrepresentations? Does one act of cheating compel the cheater to make subsequent choices that maintain the false image even at a cost? To answer these questions we employed a two-task paradigm such that in the first task the participants could benefit from false reporting of private observations whereas in the second they could benefit from making a prediction in line with their actual, rather than their previously reported observations. Thus, for those participants who inflated their report during the first task, sticking with that report for the second task was likely to lead to a loss, whereas deviating from it would imply that they had lied. Data from three experiments (total N=116) indicate that, having lied, participants were ready to suffer future loss rather than admit, even if implicitly, that they had lied.